A156 SIALIC ACID UTILIZATION IS ESSENTIAL FOR THE IN VIVO METABOLIC FITNESS OF THE ENTERIC BACTERIAL PATHOGEN CITROBACTER REDENTIUM. (15th March 2019) - Liang, Q; Yu, H; Vallance, B
Abstract: Background: The intestinal pathogens enteropathogenic and enterohemorrhagic E. coli (EPEC/EHEC) pose a significant threat to human health worldwide. These pathogens colonize host intestinal mucosal surface, forming attaching/effacing (A/E) lesions, and causing severe diarrheal disease. Currently it is unclear how resident commensals and nutritional sources in the gut influence these A/E pathogens during the course of infection. However, based on their location at the mucosal surface, they must closely interact with the intestinal mucus, which is largely composed of the highly glycosylated protein Muc2. As the most common terminal sugar on Muc2 glycans, sialic acid is actively cleaved by commensal microbes expressing sialidases, providing nutrition for themselves, as well as nearby bacteria. Recent studies suggest that host-derived sialic acid is important for the fitness of many intestinal pathogens. Citrobacter rodentium – a mouse A/E pathogen, contains genes necessary for transport and catabolism of sialic acid, however whether sialic acid plays a role in in vivo metabolism of A/E pathogens and their virulence remains unclear. Aims: To examine the role of sialic acid utilization in C. rodentium pathogenesis. Methods: A sialic acid transporter mutant of C. rodentium ( ΔnanT ) was constructed and tested in in vitro growth assays and in vivo infection, in comparison with wildtype (WT) C. rodentium . C57Bl/6 mice were infected with either WT or ΔnanT C. rodentium by oral gavage and monitored daily until euthanized at day 8 post infection (PI). In some infections, mice were pretreated with 20 mg streptomycin, 24 h before infection. Results: In vitro growth assays showed that although WT C. rodentium was able to utilize sialic acid as a sole carbon source for growth, ΔnanT was unable to do so. Moreover, ΔnanT was significantly impaired in its ability to colonize the intestines of mice, being found at very low numbers in tissues and colonic lumen (10 2 –10 3 CFU/g) at day 8 PI. In contrast, WT C. rodentium underwent rapid expansion in the colonic environment. Correspondingly, minimal histopathological damage was observed in ΔnanT infected mice. Interestingly, when mice were depleted of commensals by streptomycin, ΔnanT is able to readily colonize the intestines at comparable levels with the WT strain in terms of pathogen burdens, localization and pathology scores, suggesting the streptomycin freed up additional nutrients for ΔnanT. Conclusions: These results demonstrate that C. rodentium employs the nan transporter system for sialic acid utilization, which is essential for establishing its colonization in the mouse intestine. Moreover, these findings suggest that commensal microbes play a key role in controlling the availability of sialic acid in the colonic environment, thereby affecting the virulence and metabolism of A/E bacterial pathogens. Funding Agencies: CAG, CCC, CIHR